ANALISIS DAMPAK PERKEMBANGAN PARIWISATA TERHADAP PEREKONOMIAN MASYARAKAT (STUDI KASUS DESA TONGGING, KECAMATAN MEREK, KABUPATEN KARO, SUMATERA UTARA) - Vina Maria Ompusunggu; Rikawati Ginting Munthe (JURNAL REGIONOMIC, 2020)
Tongging Tourism Village, Brand District, Karo District, North Sumatra is a tourism village that can provide a large profit for regional income and improve the economy of the community. But in fact the population in the Brand District basically has a more dominant livelihood in the agriculture and fisheries sector. The village, if utilized and developed in the tourism sector, will attract even more domestic and foreign tourists, so that people's welfare will improve. Development basically will provide a change and impact on the surrounding objects. The purpose of this study was to determine how the impact arising from the development of tourism on the economic conditions of the surrounding community in the village of Tongging. This research uses descriptive research method with a qualitative approach. The focus of this research is the development of tourism and its impact on the state of the community's economy. The data collection and determination of the level of development are carried out by the method of collecting data in case studies, comparative studies, and documentary analysis. The data analysis technique used in this research is to use Qualitative Descriptive through several processes such as data verification, data reduction, data presentation, and drawing conclusions. The results seen that there is an impact of increasing the economic community in the development of tourism in the Village of Tongging. The positive impact of tourism development on changes in the people's economy, especially their livelihoods. Tourism provides opportunities for changes in people's livelihoods that are expanding. As with tourism development, research results show that the development of Tongging Village has an impact on the lives of surrounding communities. The number of visitors who come causes a velocity of money flow in the village of Tongging, so that the income of people both working in the tourism and non-tourism sectors increases. One of the impacts of tourism development in Tongging Village is the construction of commercial facilities in the tourism area, starting from minimarkets, hotels and souvenir centers.